UNITED KINGDOM IMPOSES SANCTIONS ON ROMAN ABRAMOVICH'S ASSETS: IS IT AN INDIRECT EXPROPRIATION? - Owen, Patrick; Amalia, Prita; Trisnamansyah, Purnama (Kanun Jurnal Ilmu Hukum, 2024)
The asset freeze imposed by the United Kingdom(UK) on Roman Abramovich raises a critical legal issue regarding its classification as indirect expropriation under international investment law. A legal gap exists in interpreting economic sanctions as acts of indirect expropriation, particularly their compatibility with protections provided under Bilateral Investment Treaties (BITs). The research addresses whether such sanctions constitute unlawful indirect expropriation and examines the protection of Abramovichs rights as a foreign investor under international law. Using a normative juridical approach, the analysis draws on international treaties, arbitration case law, and BIT provisions between Russia Federation and the United Kingdom. Findings indicate that the sanctions meet the criteria for indirect expropriation, causing substantial economic loss and disruption to Abramovichs investments, including Chelsea FC. This paper contributes to the discourse on balancing state sovereignty, regulatory powers, and investor protections, offering insights into the broader implications of politically motivated actions on foreign investments.